2020-12-11 Global transcriptomic investigation of the human macrophage response towards pathogenic/non-pathogenic mycobacteria - Mishra, Abhilasha Madhvi (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.